FAKTOR-FAKTOR PENYEBAB PERGESERAN TENAGA KERJA SEKTOR PERTANIANKE SEKTOR NON PERTANIAN DI KECAMATAN KALAWAT,KABUPATEN MINAHASA UTARA - Claudio Stylone Pesik; Gene H.M. Kapantow; Theodora M. Katiandagho (AGRI-SOSIOEKONOMI, 2016)
This study aims to determine what factors are causing the shift of labor from agriculture to non-agricultural sectors in District of Kalawat, North Minahasa. Factors of labor shift are caused by two categories: driving factors og the agricultural sector and the pull factors of non-agricultural sector so that agricultural labor to leaving work in the agricultural sector and chose to work in the non-agricultural sector. This research has been conducted since Agustus 2016 until Oktober 2016 in district of Kalawat, North Minahasa. Data collection included primary data and secondary data. Data collection method was used interview techniques. Method of selecting a sample was used sample (quota sampling). The number of respondents who would be interviewed as many 30 respondents. The characteristics of respondent are agricultural laborers have switched jobs to non-agricultural sector in district Kalawat, North Minahasa. Secondary data were obtained from the District Office Kalawat, North Minahasa. Data analysis methods applied in this study, by using descriptive method. The results of research through interviews with 30 respondents in District of Kalawat, North Minahasa. The main factors that cause labor to leave work in the agricultural sector which, because wages in the agricultural sector due to the erratic and low (43,3%) due to wages in the agricultural sector are uncertain and likely to lower the climate is influesed by the weather making revenue is often not fixed and tend to be low. As well as land became narrower and don not have any more land (43,3%) resulting from the conversion of agricultural land where settlement is also a non-agricultural activities and infrastructure development also makes labor can no longer work as farmers because it has no land for farming. Low view of work in agriculture (10%) and also due to sick and tired of working on the farm (3,3%) to make agricultural work force feel they can no longer work in the agricultural sector. It is the driving factor of the agriculutural sector which makes labor leave work in the agricultural sector.